العقد التعليمي و علاقته بالرضا الوظيفي لدى أساتذة المدرسة الإبتدائية - قدوري, سهيلة (University of Eloued جامعة الوادي, 2023)
ملخص الدراسة: تهدف الدراسة الحالية إلى التحقق من وجود علاقة ارتباطية بين العقد التعليمي و الرضا الوظيفي لدى أساتذة التعليم الإبتدائي ،ولتحقيق هذا الهدف قام الباحث بإستخدام المنهج الوصفي . و طبقت هذة الدراسة على عينة عشوائية قوامها (42) أستاذا و قد تم التوصل من خلال استخدام الإستبيان مقياس الرضا عن العقد التعليمي و من خلال استخدام الأساليب الإحصائية المتمثلة في النسبة المئوية ،،معامل ارتباط بيرسون ،اختبار ت للدلالة الإحصائية إلى مايلي : - لا توجد علاقة ارتباطية ذات دلالة احصائية بين العقد التعليمي و الرضا الوظيفي لدى أساتذة التعليم الإبتدائي. - لا توجد فروق ذات دلالة احصائية في مستوى الرضا الوظيفي لدى أساتذة التعليم الإبتدائي تعزى لمتغير الجنس(ذكر /أنثى). - لا توجد فروق ذات دلالة احصائية في مستوى الرضا الوظيفي لدى أساتذة التعليم الإبتدائي تعزى لمتغير الخبرة المهنية (أقل من 10 سنوات ،أكثر من 10 سنوات ). - لا توجد فروق ذات دلالة احصائية في مستوى العقد التعليمي لدى أساتذة التعليم الإبتدائي تعزى لمتغير الجنس(ذكر /أنثى). - توجد فروق ذات دلالة احصائية في مستوى العقد التعليمي لدى أساتذة التعليم الإبتدائي تعزى لمتغير الخبرة المهنية (أقل من 10 سنوات ،أكثر من 10 سنوات ). و اعتمادا على النتائج المتحصل عليها تبين عدم معرفة الأساتذة لإيجابيات تطبيق العقد التعليمي في عملية التعليم و مدى ايجابيته من جهة على التحصيل عند التلاميذ و عن الرضا الوظيفي لدى الأساتذة . Summary The current study aims to verify the existence of a correlation between the educational contract and job satisfaction among primary school teachers, and to achieve this goal, the researcher used the descriptive approach. This study was applied to a random sample of (42) professors, and it was reached through the use of the questionnaire, the measure of satisfaction with the educational contract, and through the use of statistical methods represented in the percentage, Pearson correlation coefficient, t-test for statistical significance to the following: - There is no statistically significant correlation between the educational contract and job satisfaction among primary school teachers. - There are no statistically significant differences in the level of job satisfaction among primary school teachers due to the gender variable (male / female). - There are no statistically significant differences in the level of job satisfaction among primary school teachers due to the variable of professional experience (less than 10 years, more than 10 years). - There are no statistically significant differences in the level of educational contract among primary school teachers due to the gender variable (male / female). - There are statistically significant differences in the level of educational contract among primary school teachers due to the variable of professional experience (less than 10 years, more than 10 years). And depending on the results obtained, it was found that the teachers did not know the positive aspects of applying the educational contract in the education process and the extent of its positiveness on the one hand on the achievement of the students and on the job satisfaction of the teachers.
تخصص علم نفس